Transurethral prostate resection for urinary retention: does age affect outcome?. (27th November 2012) - Losco, Giovanni; Mark, Stephen; Jowitt, Sharryn
Abstract Background Patients presenting in urinary retention secondary to prostatic obstruction are offered transurethral resection of the prostate (TURP) to free them from long‐term catheterization. Short‐term success is well understood, but there is scarce data about effect of age on outcome, quality of life and catheter‐free rates. Methods One hundred consecutive patients who presented in urinary retention and underwent TURP were identified. Patients were followed up for 3 years to establish the rate of catheter dependence, incontinence, pad usage and quality of life using the International Prostate Symptom Score. Results Data were obtained from 95 patients with mean age of 75.6 years and mean follow‐up of 704 days. A total of 14 had died and 23 had prostate cancer. Eighty‐seven per cent was passing urine and 13% was catheter dependent. Mean age of catheter‐dependent patients was 84.9 years compared with 74.3 years in catheter‐free men (P < 0.0001). Twenty‐four per cent of patients 80 years and older were catheter dependent (P = 0.0039), 22% with prostate cancer were catheter dependent (P = 0.15). Fifty per cent of those who had died were catheter dependent (P = 0.0002). Thirty‐one per cent of patients reported leakage of urine but only 5% reported leakage requiring pad use. Overall, the mean quality of life score was 1.08. Conclusion Outcome after TURP for urinary retention is satisfactory. Advanced age is associated with higher long‐term failure requiring catheterization, although it is still recommended in the elderly where an anaesthetic is safe. A high proportion of patients report urine leakage but the majority of this is clinically insignificant. Overall, patients report good quality of life.